2019
DOI: 10.3389/fphys.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

LSEC Fenestrae Are Preserved Despite Pro-inflammatory Phenotype of Liver Sinusoidal Endothelial Cells in Mice on High Fat Diet

Abstract: Healthy liver sinusoidal endothelial cells (LSECs) maintain liver homeostasis, while LSEC dysfunction was suggested to coincide with defenestration. Here, we have revisited the relationship between LSEC pro-inflammatory response, defenestration, and impairment of LSEC bioenergetics in non-alcoholic fatty liver disease (NAFLD) in mice. We characterized inflammatory response, morphology as well as bioenergetics of LSECs in early and late phases of high fat diet (HFD)-induced NAFLD. LSEC phenotype was evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…Capillarisation is analogous with endothelial dysfunction, in which LSEC can no longer maintain HSC quiescence in response to shear stress signals ( Deleve et al, 2008 ; Xie et al, 2012 ), and together these processes precede fibrosis ( Horn et al, 1987 ; Fraser et al, 1991 ; Pasarín et al, 2012 ; Baiocchini et al, 2019 ). A recent study, however, showed that LSEC dysfunction and loss of fenestrations following chronic metabolic stress do not always go hand in hand ( Kus et al, 2019 ). Specifically, it was shown that mice subject to high-fat diet developed non-alcoholic fatty liver disease (NAFLD)-like disease characterised by steatosis, weight gain, insulin resistance and a pro-inflammatory LSEC phenotype, yet LSEC bioenergetics and fenestrae were functionally preserved.…”
Section: Lsec Pathophysiologymentioning
confidence: 99%
“…Capillarisation is analogous with endothelial dysfunction, in which LSEC can no longer maintain HSC quiescence in response to shear stress signals ( Deleve et al, 2008 ; Xie et al, 2012 ), and together these processes precede fibrosis ( Horn et al, 1987 ; Fraser et al, 1991 ; Pasarín et al, 2012 ; Baiocchini et al, 2019 ). A recent study, however, showed that LSEC dysfunction and loss of fenestrations following chronic metabolic stress do not always go hand in hand ( Kus et al, 2019 ). Specifically, it was shown that mice subject to high-fat diet developed non-alcoholic fatty liver disease (NAFLD)-like disease characterised by steatosis, weight gain, insulin resistance and a pro-inflammatory LSEC phenotype, yet LSEC bioenergetics and fenestrae were functionally preserved.…”
Section: Lsec Pathophysiologymentioning
confidence: 99%
“…Vascular endothelial growth factor (VGEF), a hormone that functions in blood vessel growth, promotes paracrine signaling from hepatocytes and stellate cells stimulates autocrine signaling of nitric oxide (NO) from LSECs. Animals lacking VEGF tend to exhibit increased defenestration in their LSECs, suggesting that this molecule plays a mechanistic role in either their formation or maintenance (Kus et al, 2019).…”
Section: Lsec Morphologymentioning
confidence: 99%
“…Defenestration of LSECs has been reported in response to alcohol feeding in mice, however in the same study, HFD did not induce changes in fenestration [144]. During NAFLD, LSECs also displayed a pro-inflammatory phenotype, which is central to the activation of HSCs and KCs in the development of fibrosis [140,145].…”
Section: Inflammation and Fibrosis In Hccmentioning
confidence: 79%
“…Interruption of blood flow by tumor cell obstruction of the sinusoidal vasculature can lead to transient ischemia which induces tumoricidal inflammation owing to the release of ROS, nitric oxide (NO), TNF-α and interferon-γ (IFN-γ) by LSECs and KCs [153,155,157]. Similarly, HFD in mice also increased the levels of reactive ROS produced from LSECs [158], and increasing NAFLD severity was associated with a pro-inflammatory gene expression signature in LSECs which included increased COX-2, NOX-2 and IL-6 levels [145]. HFD-induced CLD could therefore potentiate elimination of disseminated tumor cells invading the liver sinusoid.…”
Section: Inflammation In the Microvascular Phase Of Crc Liver Metastasismentioning
confidence: 99%
See 1 more Smart Citation